Self-Transcendence of Japanese Female Breast Cancer Patients with Hereditary Breast and Ovarian Cancer Syndrome - Sanae Aoki; Sawa Fujita (Elsevier, 2021)
Objective: The present study examined self-transcendence of Japanese female breast cancer patients with hereditary breast and ovarian cancer (HBOC) syndrome. Methods: Semi-structured interviews were conducted with 13 women with HBOC in their thirties to sixties, who consented to participate in the study. The obtained data were analyzed using a modified grounded theory approach. Results: The analysis yielded seven categories of self-transcendence in women with HBOC: (1) the ability to face oneself while seeking optimal strategies to continue living; (2) the ability to come to terms with blood conditions inherited from previous generations; (3) the ability to use one's own experiences as a patient with HBOC to help others; (4) the ability to share mutual support with others; (5) the ability to accept the diverse views on HBOC; (6) the ability to break free from fixed ideas and live with HBOC; and (7) the ability to live with future perspectives. Conclusions: The self-transcendence of Japanese female breast cancer patients with HBOC can be described as not giving up; confronting one's lineage, which is passed down from generation to generation, even as one is haunted and emotionally affected by the lifelong risk of developing cancer or facing death; and valuing not just oneself but also others through interactions with them. These abilities formed the foundation for the self-transcendence of the women in this study. In addition, because the women with this condition started valuing not just themselves but also others, they developed the ability to accept the diverse views surrounding HBOC and to coexist with their condition while being forward-looking.